2009
DOI: 10.1021/ja808255d
|View full text |Cite
|
Sign up to set email alerts
|

Binding Mechanism of an SH3 Domain Studied by NMR and ITC

Abstract: Complexes between Src-homology 3 domains and proline-rich target peptides can have lifetimes on the order of milliseconds, making them too short-lived for kinetic characterization by conventional methods. Nuclear magnetic resonance (NMR) dynamics experiments are ideally suited to study such rapid binding equilibria, and additionally provide information on partly bound intermediate states. We used NMR together with isothermal titration calorimetry (ITC) to characterize the interaction of the SH3 domain from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 105 publications
9
118
3
1
Order By: Relevance
“…We previously used NMR and ITC to study the binding kinetics of the SH3 domain from the Fyn tyrosine kinase. We showed that this protein binds a type I target peptide in a two-state manner with millisecond time scale kinetics and a temperature dependence of k on that is consistent with diffusion-limited association (33). In the current study, we have focused on how positively charged residues within the SH3 binding motif and negatively charged residues in the binding site on the SH3 domain interact to influence association kinetics.…”
mentioning
confidence: 74%
See 3 more Smart Citations
“…We previously used NMR and ITC to study the binding kinetics of the SH3 domain from the Fyn tyrosine kinase. We showed that this protein binds a type I target peptide in a two-state manner with millisecond time scale kinetics and a temperature dependence of k on that is consistent with diffusion-limited association (33). In the current study, we have focused on how positively charged residues within the SH3 binding motif and negatively charged residues in the binding site on the SH3 domain interact to influence association kinetics.…”
mentioning
confidence: 74%
“…NMR-derived Binding Kinetics-We previously characterized the binding kinetics of the RR peptide using NMR and ITC over a temperature range of 10 -50°C (33). In this prior work, we employed both CPMG and ZZ magnetization exchange NMR experiments at 20°C, obtaining very similar values for k off : 11.2 and 12.8 s Ϫ1 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Global or cluster fits (assuming shared k ex values and populations) of groups of nuclei are therefore justified on physical grounds. Global fits have the advantage of increasing the precision with which exchange parameters are estimated (Demers & Mittermaier, 2009) but care must be taken with respect to how grouping is performed. Grouping can be performed by simply grouping nuclei, which yields exchange parameters similar to those obtained when nuclei are treated individually.…”
Section: Data Clustering To Increase Precision Of Fitted Parametersmentioning
confidence: 99%